The Philosophical Values of Kawung Batik Motif in Contemporary Batik Painting - Adam Wahida; Endang Sri Handayani; Slamet Supriyadi (Institut Seni Indonesia Denpasar, 2020)
As one of the classic Javanese batik, the Kawung batik motif contains philosophical values ​​that teach life guidelines for humans, such as gratitude, religiosity, respect for nature, and togetherness. These philosophical values ​​are still relevant to the current situation, so it is interesting to be used as a source of ideas for the creation of contemporary paintings. This article is the result of research that aims to describe the philosophical values ​​of the Kawung batik motif as a source of ideas and the process of creating contemporary batik paintings. The method is descriptive qualitative with the type of art creation research. The stages include: 1) gathering information about the Kawung batik motif, 2) exploring ideas based on the philosophical meaning of the Kawung batik motif, 3) making a design sketch, 4) realizing the sketch into a painting, 5) describing the shape of the painting created. The results of this study are 1) a description of the philosophical meaning of Kawung batik motifs, 2) a description of the process of creating contemporary batik painting works, 3) a description of the forms of contemporary batik painting works that contain philosophical values ​​of Kawung batik motifs. The results of this study indicate that the batik painting produced has a local character and represents the soul of the times. Thus, it is evident that the local wisdom values ​​of traditional culture can be developed and harmonized with contemporary culture.